Conventional and novel "omics"‐based approaches to the study of carbon nanotubes pulmonary toxicity. (26th February 2018) - Ventura, Célia; Sousa‐Uva, António; Lavinha, João; Silva, Maria João
Abstract : The widespread application of carbon nanotubes (CNT) on industrial, biomedical, and consumer products can represent an emerging respiratory occupational hazard. Particularly, their similarity with the fiber‐like shape of asbestos have raised a strong concern about their carcinogenic potential. Several in vitro and in vivo studies have been supporting this view by pointing to immunotoxic, cytotoxic and genotoxic effects of some CNT that may conduct to pulmonary inflammation, fibrosis, and bronchioloalveolar hyperplasia in rodents. Recently, high throughput molecular methodologies have been applied to obtain more insightful information on CNT toxicity, through the identification of the affected biological and molecular pathways. Toxicogenomic approaches are expected to identify unique gene expression profiles that, besides providing mechanistic information and guiding new research, have also the potential to be used as biomarkers for biomonitoring purposes. In this review, the potential of genomic data analysis is illustrated by gene network and gene ontology enrichment analysis of a set of 41 differentially expressed genes selected from a literature search focused on studies of C57BL/6 mice exposed to the multiwalled CNT Mitsui‐7. The majority of the biological processes annotated in the network are regulatory processes and the molecular functions are related to receptor‐binding signalling. Accordingly, the network‐annotated pathways are cell receptor‐induced pathways. A single enriched molecular function and one biological process were identified. The relevance of specific epigenomic effects triggered by CNT exposure, for example, alteration of the miRNA expression profile is also discussed in light of its use as biomarkers in occupational health studies. Environ. Mol. Mutagen. 59:334–362, 2018. © 2018 Wiley Periodicals, Inc.